Case Report: Multiple immune related adverse events in a patient with metastatic melanoma - Varada, Neilmegh L.; Yang, Olivia; Savage, David J. (Frontiers in Immunology, 2025)
IntroductionImmune related adverse events (irAEs) are a well-recognized potential complication of immunotherapy treatment. Immunotherapy works at the level of T-cells and tumors to blunt checkpoints that normally suppress overactivation of the immune response. While this leads to a therapeutic benefit in many cases, the dysregulated immune system can also attack healthy parts of the body, leading to toxicity. For stage IV melanoma, combination checkpoint inhibition with multiple drugs agents is the preferred frontline treatment, however, this can increase the risk of irAEs. This case describes a person treated with the Lymphocyte-activation gene 3 (LAG-3) inhibitor relatlimab and the Programmed cell death protein 1 (PD-1) inhibitor nivolumab for stage IV melanoma who subsequently developed four distinct and significant toxicities.Case descriptionAn 80-year-old male with a history of melanoma was diagnosed with stage IV melanoma. He was started on treatment with relatlimab/nivolumab. One month later he began to experience Liver Function Test (LFT) elevations that were < 2x upper limit of normal (ULN). After Cycle 2, labs showed worsening of transaminitis, this time nearly 2x ULN. He started on a steroid taper, returning his LFTs to normal, and he was treated with Cycle 3. In the next month, LFTs worsened to >3x ULN, he developed a rash, and the patient developed primary hypothyroidism. Treatment was discontinued and he started thyroid hormone replacement. One month after cycle 3 was given, he was admitted with an acute heart failure exacerbation secondary to myocarditis. Multiple attempts to taper steroids were made, but LFTs worsened each time. He was ultimately started on mycophenolate mofetil in three months later and tapered off steroids completely. His LFTs, rash, and myocarditis resolved. Patient remains on active surveillance with permanent discontinuation of immunotherapy.DiscussionThis patient developed grade 2 primary hypothyroidism, grade 3 myocarditis, grade 2 dermatitis, and grade 3 hepatitis from three treatments with relatlimab/nivolumab. There were some early indications of LFT changes prior to cycle 3, but symptoms were most appreciable after cycle 3. The relatlimab/nivolumab combination was selected because of the lower incidence of irAEs reported in Relativity-047 compared to the CheckMate trials with ipilimumab/nivolumab. This case demonstrates the challenges of managing multiple irAEs in a single patient. It also is an acute reminder that immune activation can take time, and that irAEs can persist for a long period of time or indefinitely after treatment is discontinued.ConclusionsirAEs occur in up to 30% of patients who receive checkpoint immunotherapy for stage IV melanoma treatment. It is possible to have multiple toxicities in a single patient. Management requires prolonged immune suppression, correction of endocrine abnormalities, and coordination with a multidisciplinary team. Physicians should have a low threshold to pause treatment at early laboratory signs of an evolving irAE.